2014
DOI: 10.1111/ane.12282
|View full text |Cite
|
Sign up to set email alerts
|

The associations between fatigue, apathy, and depression in Parkinson's disease

Abstract: Although the pathophysiology of fatigue and apathy in PD is clearly multifactorial, in a proportion of PD patients, these symptoms are associated with depression, dopaminergic depletion in the mesocorticolimbic structures, and disruption of the prefrontal cortex-basal ganglia axis. Therefore, in some PD patients, adequate management of depression and optimal dopaminergic medication may improve both fatigue and apathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 36 publications
7
80
1
Order By: Relevance
“…Multiple, but not all, studies in PD show a significant correlation between depression and fatigue. 8 Anxiety and apathy also correlate with fatigue 21,22 but many fatigued patients are not depressed, anxious, or apathetic. 8 Several studies suggest that cognitive performance, frontal lobe activity, and self-reported cognitive impairment are associated with fatigue.…”
Section: Clinical Review Of Fatigue In Pdmentioning
confidence: 99%
“…Multiple, but not all, studies in PD show a significant correlation between depression and fatigue. 8 Anxiety and apathy also correlate with fatigue 21,22 but many fatigued patients are not depressed, anxious, or apathetic. 8 Several studies suggest that cognitive performance, frontal lobe activity, and self-reported cognitive impairment are associated with fatigue.…”
Section: Clinical Review Of Fatigue In Pdmentioning
confidence: 99%
“…Fatigue is regarded as an independent non-motor symptom in PD, and its etiology is multifactorial [27, 28]. The striato-thalamo-frontal cortical pathway is strongly associated with central fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst apathy is a common syndrome associated with altered motivation [2, 12], it is also frequently comorbid with other states which may have symptoms of reduced motivation, particularly depression, anhedonia and fatigue [3, 4, 15, 16]. This raises the question of the extent to which apathy can be meaningfully distinguished from these other conditions and whether they might perhaps be associated with discrete dimensions of apathy in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%